Emergence of multidrug resistant and extensively drug resistant community acquired uropathogens in Dhaka city, Bangladesh. (Bangladesh Journal of Medical Microbiology, 2017)
Because of indiscriminate, inadequate and irrational usage of antimicriobials, the sensitivity pattern of community acquired uropathogens is changing drastically, specifically in developing countries, such as Bangladesh. This study was undertaken to investigate the profile of common uropathogens in community settings and to evaluate their antimicrobial resistance profile in order to categorize them into multidrug resistant (MDR), extensively drug resistant (XDR) and pandrug resistant (PDR) organisms.Total 800 urine samples were collected from symptomatic UTI cases and processed in the Department of Microbiology of DMC following standard microbiological methods. Antimicrobial susceptibility pattern was determined by Kirby Bauer Disc diffusion method following Clinical and Laboratory Standards Institute (CLSI) guidelines.Simultaneously, the percentage prevalence of MDR, XDR, and PDR isolates were also determined. Out of the 800 urine samples screened, 150 (18.75%) samples yielded significant growth. The most common bacterial isolate was Esch.coli (60%), followed by Klebsiella species (13.33%). A significantly high resistance was noted to the beta-lactam group of antimicrobials, fluoroquinolones and cotrimoxazole, both by the gram-negative bacilli (GNB) as well as gram-positive cocci (GPC). However nitrofurantoinwas found to be most effective oral drug against both GNB and GPC. Out of total 150 bacterial strains studied, 106 (70.67%) bacterial strains were MDR, 21 (14%) strains were XDR, and no PDR was detected.So, close monitoring of MDR, XDR, or even PDR must be done by all clinical microbiology laboratories to implement effective measures to reduce the menace of antimicrobial resistance.Bangladesh J Med Microbiol 2015; 9 (2): 7-12